A novel broad-spectrum antibacterial and anti-malarial Anopheles gambiae Cecropin promotes microbial clearance during pupation. - Cairé Barreto; Victor Cardoso-Jaime; George Dimopoulos (PLoS Pathogens)
Anophelinae mosquitoes are exposed to a variety of microbes including Plasmodium parasites that cause malaria. When infected, mosquitoes mount versatile immune responses, including the production of antimicrobial peptides. Cecropins are one of the most widely distributed families of antimicrobial peptides in insects and all previously studied Anopheles members are playing roles in adult mosquito immunity. We have identified and characterized a novel member of the Anopheles gambiae cecropin family, cecropin D (CecD), that is uniquely expressed and immune-responsive at late larval stages to promote microbial clearance through its broad-spectrum antibacterial activity during larval-pupal developmental transition. Interestingly, Cecropin D also exhibited highly potent activity against Plasmodium falciparum sporozoites, the malaria parasite stage that is transmitted from mosquitoes and infects humans and thereby holds promise as a malaria transmission-blocking agent. Finally, we have defined unequivocal cecropin-specific molecular signatures to systematically organize the diversity of the cecropin family in malaria vectors.